2014
DOI: 10.1016/j.econlet.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Are elections debt brakes? Evidence from French municipalities

Abstract: We show that voters are fiscal conservatives, although in the long run only: while the average (over the mandate) level of debt has a negative impact on the probability of reelection, pre-election debt accumulation by incumbents increases their probability of reelection. As the negative impact is larger the higher the debt level, it compensates the short run effect. Elections thus appear as a disciplining device, even if a weak one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…However, Blais and Nadeau (1992), Kiewiet and Szalaky (1996) and Dickson and Yu (1997) found that conservative parties present lower debt levels. Balaguer-Coll et al (2015), Brender (2003) and Cassette and Farvaque (2014) showed that high debt levels negatively affect governments' re-election probabilities.…”
Section: Political Ideology (Sign)mentioning
confidence: 99%
“…However, Blais and Nadeau (1992), Kiewiet and Szalaky (1996) and Dickson and Yu (1997) found that conservative parties present lower debt levels. Balaguer-Coll et al (2015), Brender (2003) and Cassette and Farvaque (2014) showed that high debt levels negatively affect governments' re-election probabilities.…”
Section: Political Ideology (Sign)mentioning
confidence: 99%
“…Using local or regional data to examine whether budget manipulation affects the incumbent's re-election chances, Akhmedov and Zhuravskaya (2004), Veiga and Veiga (2007b), Sakurai and Menezes-Filho (2008), Drazen and Eslava (2010), Aidt et al (2011), Jones et al (2012, Litschig and Morrison (2012), Cassette andFarvaque (2014), Balaguer-Coll et al (2015), Bracco et al (2015), and Repetto (2018) find a positive relationship between changing the spending composition of the budget (mostly in the way of spending more on capital expenditures, sometimes on current expenditures) and the probability of re-election. Klein (2010) and Chortareas et al (2016) report a positive effect at the local level too, but in terms of total spending rather than budget composition, whereas Brender (2003) finds no significant impact at all.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, in 1990, the banking crisis in Sweden plummeted private investment by 35%, with GDP falling for three consecutive years, a total of −5.1% in 1991-1993, and overall the country went into a significant recession during the same period (Englund, 2016;Stockhammar & Österholm, 2016). The studies by Cassette and Farvaque (2014), Kirikkaleli and Onyibor (2020), and Kirikkaleli (2016) have reported adverse effects of financial risk from the post-World War II period until the present time, the most significant challenge faced by the country's economy. On the contrary, Arcand and Fafchamps (2012), Cecchetti and Kharroubi (2012), and Rousseau and Wachtel (2011), among other studies, have failed to find a definite link between financial risk and economic stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the post-World War II period until the present time, studies have argued that the most significant challenge faced by the global economy and mainly Europe and Africa is a global economic crisis (Cassette & Farvaque, 2014). A similar situation is the Arab Spring, which escalated protests and suspended constitution across the Northern African countries (Acemoglu et al, 2018;Hermida et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%